Expression of annexin-A1 and galectin-1 anti-inflammatory proteins and mRNA in chronic gastritis and gastric cancer - Jorge, Yvana Cristina [UNESP]; Mataruco, Mayra Mioto [UNESP]; Araújo, Leandro Pires [UNESP]; Rossi, Ana Flávia Teixeira [UNESP]; De Oliveira, Juliana Garcia [UNESP]; Valsechi, Marina Curado [UNESP]; Caetano, Alaor; Miyazaki, Kenji; Fazzio, Célia Sebastiana de Jesus; Thomé, Jorge Alberto; Rahal, Paula [UNESP]; Oliani, Sonia Maria [UNESP]; et al. (Hindawi, 2013)
Objective. The anti-inflammatory proteins annexin-A1 and galectin-1 have been associated with tumor progression. This scenario prompted us to investigate the relationship between the gene and protein expression of annexin-A1 (ANXA1/AnxA1) and galectin-1 (LGALS1/Gal-1) in an inflammatory gastric lesion as chronic gastritis (CG) and gastric adenocarcinoma (GA) and its association with H. pylori infection. Methods. We analyzed 40 samples of CG, 20 of GA, and 10 of normal mucosa (C) by the quantitative real-time PCR (qPCR) technique and the immunohistochemistry assay. Results. High ANXA1 mRNA expression levels were observed in 90% (36/40) of CG cases (mean relative quantification RQ = 4.26 ± 2.03) and in 80% (16/20) of GA cases (mean RQ = 4.38 ± 4.77). However, LGALS1 mRNA levels were high (mean RQ = 2.44 ± 3.26) in 60% (12/20) of the GA cases, while low expression was found in CG (mean RQ = 0.43 ± 3.13; P < 0.01). Normal mucosa showed modest immunoreactivity in stroma but not in epithelium, while stroma and epithelium displayed an intense immunostaining in CG and GA for both proteins. Conclusion. These results have provided evidence that galectin-1 and mainly annexin-A1 are overexpressed in both gastritis and gastric cancer, suggesting a strong association of these proteins with chronic gastric inflammation and carcinogenesis. © 2013 Yvana Cristina Jorge et al.
Keywords: galectin 1; lipocortin 1; messenger RNA; adult; chronic gastritis; controlled study; disease association; female; gene expression; Helicobacter infection; Helicobacter pylori; human; human cell; immunohistochemistry; immunoreactivity; major clinical study; male; priority journal; protein expression; real time polymerase chain reaction; stomach adenocarcinoma; aged; gastritis; genetics; in vitro study; metabolism; middle aged; pathogenicity; pathophysiology; reverse transcription polymerase chain reaction; stomach tumor; Adult; Aged; Annexin A1; Female; Galectin 1; Gastritis; Helicobacter Infections; Humans; Male; Middle Aged; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stomach Neoplasms